Share
Explore BrainMass

Using Foil Method to find the product of an expression

Use the foil method to find the product: (5y^3w^2 + 2)(2y^3w^2 + 3z)

Attachments

Solution Preview

=====================================================

FOIL method:

Every term in the first binomial gets multiplied by every term in the second binomial.

Consider (a + b) (c+d). ...

Solution Summary

First the product of a general expression was found using the foil method. This general result was used to find the product of a given expression.

$2.19